Assessment of occupational safety and health practices in selected laboratories at SIRIM Bhd Shah Alam / Rabiatul Adawiyah Md Hasim - Rabiatul Adawiyah, Md Hasim (2017)
This study was aimed to assess the occupational safety and health practices in laboratory in SIRIM Berhad Shah Alam by Observation, Interview and questionnaire surveys. There are two type laboratories involves in this research which are chemical and biology laboratories. The method use to determine the compliance was by using Hazard Identification, Risk Assessment and Risk Control (HIRARC) procedure which make the identification, collection and analyze the parameter easier. Four laboratories has been selected which are (1) Applied Chemical Laboratory, (2) Analytical Biochemical Laboratory, (3) Microbial Isolation and Screening Laboratory and (4) Bacteriology Laboratory. Laboratory practise was reviewed and evaluated depends on its SOPs, MSDS, OSH awareness, implementation and practices and emergency response plan. The results shows that the laboratory related standard does not directly control what the employees are performing in their laboratories, instead it governs on how the employees execute their tasks. With this, the selected laboratories in IBRC at SIRIM Bhd Shah Alam in a way have committed towards quality in safety and health and hope to keep laboratories competent of providing a safe working environment. For future reference, the results from this assessment may also aid organisations in terms of monitoring and review of their existing occupational safety, health and emergency response in a workplace.